Profiling secondary metabolites and antioxidant activity of tea mistletoe leaves (Scurrula artopurpurea (Bl.) Danser) in Nglinggo, Kulon Progo, Yogyakarta - Dwi Aditiyarini; Ratih Restiani; Evieyana Evieyana (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.